Evolutionary trade-offs between testes size and parenting in Neotropical glassfrogs - Valencia-Aguilar, Anyelet [UNESP] (2024)
In males, large testes size signifies high sperm production and is commonly linked to heightened sperm competition levels. It may also evolve as a response to an elevated risk of sperm depletion due to multiple mating or large clutch sizes. Conversely, weapons, mate or clutch guarding may allow individuals to monopolize mating events and preclude sperm competition, thereby reducing the selection of large testes. Herein, we examined how paternal care, sexual size dimorphism (SSD), weaponry and female fecundity are linked to testes size in glassfrogs. We found that paternal care was associated with a reduction in relative testes size, suggesting an evolutionary trade-off between testes size and parenting. Although females were slightly larger than males and species with paternal care tended to have larger clutches, there was no significant relationship between SSD, clutch size and relative testes size. These findings suggest that the evolution of testes size in glassfrogs is influenced by sperm competition risk, rather than sperm depletion risk. We infer that clutch guarding precludes the risk of fertilization by other males and consequently diminishes selective pressure for larger testes. Our study highlights the prominent role of paternal care in the evolution of testes size in species with external fertilization.